SITE SUITABILITY ANALYSIS FOR COMMUNITY-BASED TROPICAL SEA CUCUMBER HOLOTHURIA SCABRA GROW-OUT IN NORTH SULAWESI WATERS - Rizqi, Marenda Pandu; Supono, - (Marine Research in Indonesia, 2019)
North Sulawesi, a region that has experienced a decreasing population of commercial sea cucumbers in Indonesia, has recently been designated an aquaculture development area. Recent developments of sea cucumber Holothuria scabra hatchery technology have successfully enabled the small-scale enterprise to produce hatchery-reared sandfish for restocking purposes. However, the grow-out phase requires considerable resources including ex-situ grow-out sites, labor, and distribution. This study aims to investigate the suitability of some potential grow-out sites for juvenile H. scabra in North Sulawesi waters. Three traditional sea cucumber fishing grounds in coastal areas of North Minahasa regency in North Sulawesi, i.e., Tanjung Merah, Tasikoki and Makalisung, were examined to determine their suitability as a grow-out site. Several criteria encompassing bioecological (native sea cucumber population, seagrass bed population, competitor/predator), environmental (substrate, protection to weather, water quality, tidal cycle), and technical/support (access, safety, labor) were assessed in each site. Site suitability analysis using a multi-criteria decision-making tool, Analytical Hierarchy Process (AHP), shows that Tasikoki has the highest suitability score (48.94%) followed by Tanjung Merah (27.18%) and Makalisung (23.88%). Tasikoki scores higher than the two other sites in 7 out of 11 sub-criteria, including native sandfish population, seagrass species, substrate, weather protection, safety, and community support. Our finding suggests that Tasikoki is bioecologically, environmentally, and technically the best potential site to be developed for H. scabra juvenile grow-out.